A Cluster Analysis of Home Builders Based on Financial Resource Allocation - Suriyanon, Natee; Phansri, Watcharit (Journal of Architectural/Planning Research and Studies (JARS), 2020)
This research adopted a cluster analysis to cluster 23 home builders, based on proportion of financial resource allocation, into 3 groups. The results of the analysis of each group revealed that the home builder group 1 mainly focused on the competitive advantage from having high liquidity and investment in permanent assets in order to cut costs and enhance revenues. The home builder group 2 paid attention to other current assets such as construction equipment, in order to create the competitive advantage from having low construction costs. The home builder group 3 principally attempted to create the market from expanding debtor collection periods of accounts receivable, by mobilizing external financial sources to increase liquidity. The comparison of rate of return on equity among the three groups showed that the home builder group 2 possessed more potential to receive a little higher rate than that of the home builder group 1. Besides, the rate of return on equity of the home builder group 3 had high variation, compared to that of group 1 and 2.